VIBRATING TABLES WITH THE SPATIAL OSCILLATIONS OF THE MOVING FRAME TECHNOLOGICAL PROPERTIES FOR FORMING REINFORCED CONCRETE PRODUCTS - Nesterenko, Mykola; Nesterenko, Mykola; Orysenko, Olexandr; Sklyarenko, Taras (Academic journal Industrial Machine Building Civil Engineering, 2019)
A brief description of vibration tables with spatial oscillations of a moving frame and comparison of their technologicalpossibilities depending on their constructive execution are given. The methodology for evaluating the technological andstructural parameters of the vibration tables is also presented based on the use of a dimensionless complex parameter that enables to evaluate the consumer qualities of the vibrating tables, their technical level and competitiveness during the designand operation stage. The vibrating machines constructive designs schemes, their characteristics and the description of thescope of application are presented, which enables designers and manufacturers to orientate themselves in the variety of currently used vibration machines with spatial oscillations of the moving frame for the formation of the same type of reinforcedconcrete products.
Keywords: vibration table; vibration exciter; forming concrete reinforced products